2009
DOI: 10.1021/ja9029076
|View full text |Cite
|
Sign up to set email alerts
|

Rate Constants for Peroxidation of Polyunsaturated Fatty Acids and Sterols in Solution and in Liposomes

Abstract: Rate constants for autoxidation propagation of several unsaturated lipids in benzene solution at 37°C and in phosphatidylcholine liposomes were determined by a linoleate radical clock. This radical clock is based on competition between hydrogen atom abstraction by an intermediate peroxyl radical derived from linoleic acid that leads to a trans,cis-conjugated hydroxyoctadecadienoic product and β–fragmentation of the same peroxyl that gives the trans,trans-product hydroxyoctadecadienoic acid. Rate constants dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
219
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(236 citation statements)
references
References 64 publications
12
219
0
5
Order By: Relevance
“…The LPO process in bulk phospholipids depends on their unsaturation. [54][55][56][57] Thus, it has been hypothesised that the membrane response to cigarette smoke should differ, depending on initial unsaturation of the PC material being used for liposome preparations. There exists only a few reports on cell membranes and liposomes exposed to cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…The LPO process in bulk phospholipids depends on their unsaturation. [54][55][56][57] Thus, it has been hypothesised that the membrane response to cigarette smoke should differ, depending on initial unsaturation of the PC material being used for liposome preparations. There exists only a few reports on cell membranes and liposomes exposed to cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…PL are the basic lipid components of plasmatic cell membranes and membranes of subcellular organelles of animals, plants, and microorganisms. Phosphatidylcholines (1,2-diacyl-sn-glycero-3-phosphocholines, lecithins) are the most widely used; they are present in large amounts in myocardium, liver, kidneys, and egg yolk [56]. In lecithin molecules, anionic phosphate and cationic choline (tetraalkylammonium) groups are connected via a zwitterionic bond to form a neutral polar head.…”
Section: Phospholipid Oxidationmentioning
confidence: 99%
“…Lecithins are easily dissolved in organic solvents to yield compact reverse micelles [60,61]. In aqueous solutions, lecithin forms multilamellar liposomes or vesicles under the action of ultrasound dispersion [12,56,62]. Using the DLS method, it was found that, at egg lecithin concentrations 10-90 mg/mL, the size of microaggregates observed are equal to 5-6 nm in organic solvents and in water, liposomes are formed with a wide size distribution of 60-1000 nm.…”
Section: Phospholipid Oxidationmentioning
confidence: 99%
“…1.4% 2-propanol and 0.1% acetic acid in hexanes) with selective reaction monitoring [24,25]. Among these HPLC-MS analyses, the reactions that have large KODEs (corresponding ketones from HODEs) were also analysed [25] in reactions with D 2 -Lin: Lin ratios varying from 0 to 9.…”
Section: Radical Clock and Co-oxidation Experimentsmentioning
confidence: 99%
“…To determine the effect of the isotope reinforcement on the propagation rate constants of Lin autoxidation as compared to that of 11,11-D 2 -Lin, we performed parallel clocking experiments utilizing a linoleate peroxyl radical clock [6,23,24], as well as competition experiments by co-oxidizing 11,11-D 2 -Lin and Lin in solution.…”
Section: Kinetic Measurements Reveal a Large Kie For The Chain Reactimentioning
confidence: 99%